Genetic Diversity and Population Structure of Jubaea chilensis, an Endemic and Monotype Gender from Chile, Based on SNP Markers - Jara-Arancio, Paola; da Silva Carvalho, Carolina; Carmona-Ortiz, Martin R.; Bustamante, Ramiro O.; Schmidt Villela, Priscilla M.; da Silva Andrade, Sonia C.; Pena-Gomez, Francisco T.; Gonzalez, Luis A.; Fleury, Marina (My University, 2022)
Jubaea chilensis (Molina) Baill., also named Chilean palm, is an endemic species found in the coastal area of Mediterranean sclerophyllous forest in Chile. It has a highly restricted and fragmented distribution along the coast, being under intense exploitation and anthropogenic impact. Based on 1038 SNP markers, we evaluated the genetic diversity and population structure among six J. chilensis natural groups encompassing 96% of the species distribution. We observed low levels of genetic diversity, a deficit of heterozygotes (mean H-E = 0.024; H-O = 0.014), and high levels of inbreeding (mean F-IS = 0.424). The fixation index (F-ST) and Nei's genetic distance pairwise comparisons indicated low to moderate structuring among populations. There was no evidence of isolation by distance (r = -0.214, p = 0.799). In the cluster analysis, we observed a closer relationship among Culimo, Cocalan, and Candelaria populations. Migration rates among populations were low, except for some populations with moderate values. The K value that best represented the spatial distribution of genetic diversity was Delta K = 3. Habitat fragmentation, deterioration of the sclerophyllous forest, lack of long-distance dispersers, and a natural regeneration deficit may have driven inbreeding and low levels of genetic diversity in the palm groves of J. chilensis. Although extant populations are not at imminent risk of extinction, the rate of inbreeding could increase and migration could decrease if the effects of climate change and human impact become more acute.
Keywords: genetic diversity; jubaea chilensis; population structure; snp; neotropical palm